"Framing fan fiction: Literary and social practices in fan fiction communities," by Kristina Busse - Abby Waysdorf (Transformative Works and Cultures, 2019)
Review of Kristina Busse. Framing fan fiction: Literary and social practices in fan fiction communities. Iowa City: University of Iowa Press, 2017, paperback, $45 (262p) ISBN 978-9888390809.